Solid-state batteries and solid-state battery systems

JP7632352B2Active Publication Date: 2025-02-19TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022037030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-10
Publication Date
2025-02-19
Estimated Expiration
2042-03-10

Smart Images

  • Figure 0007632352000003
    Figure 0007632352000003
  • Figure 0007632352000004
    Figure 0007632352000004
  • Figure 0007632352000005
    Figure 0007632352000005
Patent Text Reader

Abstract

To provide a solid-state battery that can suppress capacity reduction due to charge / discharge cycles.SOLUTION: A solid-state battery according to the present disclosure includes a negative electrode having a negative electrode current collector, a positive electrode, and a solid electrolyte layer disposed between the negative electrode and the positive electrode, and utilizes a precipitation-dissolution reaction of metallic lithium as a negative electrode reaction. An Mg layer containing Mg and an Al layer containing Al are arranged in this order from the negative electrode current collector side between the negative electrode current collector and the solid electrolyte layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to solid-state batteries and solid-state battery systems. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway.

[0003] Among batteries, lithium-ion batteries have attracted attention because they use lithium, which has the highest ionization tendency among metals, as a carrier, and can provide high output voltage. Solid-state batteries, which use a solid electrolyte instead of an organic solvent-containing electrolyte between the positive and negative electrodes, have attracted attention because they can provide high volumetric energy density.

[0004] For example, Patent Document 1 discloses that, for a negative electrode layer for an all-solid-state secondary battery including a negative electrode current collector and a first negative electrode active material layer including a lithium metal composite, a metal thin film or a semi-metal thin film including one or more elements selected from gold, silver, magnesium, zinc, silicon, tin, platinum, palladium, aluminum, and bismuth is included between the negative electrode current collector and the first negative electrode active material layer.

[0005] Patent Document 2 discloses an all-solid-state battery having a positive electrode, a solid electrolyte, and a negative electrode, in which the negative electrode includes a negative electrode member, and the negative electrode member is formed by coating the surface of a stainless steel mesh with at least one metal selected from the group consisting of Mg, Ag, Al, and Au. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2021-077640 A [Patent Document 2] JP 2019-087420 A Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 1 discloses that metallic Li is precipitated on the negative electrode current collector by charging, forming a metallic Li layer (second negative electrode active material layer). In this way, in a solid-state battery that utilizes the precipitation-dissolution reaction of metallic lithium as the negative electrode reaction, the metallic lithium layer precipitated on the negative electrode current collector dissolves from the solid electrolyte layer side during discharge. Therefore, as discharge progresses, gaps are likely to occur between the negative electrode current collector and the solid electrolyte layer. As a result, capacity reduction is likely to occur, particularly with repeated charging and discharging.

[0008] The present disclosure has been made in consideration of the above problems, and has as its main object to provide a solid-state battery capable of suppressing a decrease in capacity due to charge / discharge cycles. [Means for solving the problem]

[0009] In order to solve the above problems, the present disclosure provides a solid-state battery that includes a negative electrode having a negative electrode current collector, a positive electrode, and a solid electrolyte layer disposed between the negative electrode and the positive electrode, and utilizes a deposition-dissolution reaction of metallic lithium as a negative electrode reaction, in which a Mg layer containing Mg and an Al layer containing Al are disposed in this order from the negative electrode current collector side between the negative electrode current collector and the solid electrolyte layer.

[0010] According to the present disclosure, a solid-state battery capable of suppressing capacity reduction due to charge / discharge cycles is obtained by providing a Mg layer containing Mg and an Al layer containing Al between a negative electrode current collector and a solid electrolyte layer in this order from the negative electrode current collector side.

[0011] In the above disclosure, a metallic Li layer may be provided between the Mg layer and the solid electrolyte layer.

[0012] In the above disclosure, the Mg layer may have a thickness of 0.5 μm or more and 5 μm or less.

[0013] In the above disclosure, the Al layer may have a thickness of 100 nm or more and 500 nm or less.

[0014] In the above disclosure, the Mg layer and the Al layer may each be a vapor deposition layer.

[0015] In the above disclosure, the solid electrolyte layer may include a sulfide solid electrolyte.

[0016] The present disclosure also provides a solid-state battery system including: a solid-state battery having a negative electrode with a negative electrode current collector, a positive electrode, and a solid electrolyte layer disposed between the negative electrode and the positive electrode, utilizing a deposition-dissolution reaction of metallic lithium as a negative electrode reaction; and a discharge control device that controls discharge of the solid-state battery, wherein the solid-state battery has, between the negative electrode current collector and the solid electrolyte layer, a Mg layer containing Mg and an Al layer containing Al, in this order from the negative electrode current collector side, and the discharge control device controls a lower limit voltage of the solid-state battery during discharge to be higher than 3.0 V.

[0017] According to the present disclosure, a solid-state battery system is provided in which the lower limit voltage during discharging of a specific solid-state battery is controlled to prevent the battery from being completely discharged.

[0018] In the above disclosure, the discharge control device may control a lower limit voltage of the solid-state battery during discharge to 3.5 V or less. Effect of the Invention

[0019] The present disclosure has an effect of providing a solid-state battery capable of suppressing a decrease in capacity due to charge / discharge cycles. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of a solid-state battery according to the present disclosure. [Diagram 3] 2 shows charge / discharge curves of the solid-state battery obtained in Example 1. [Figure 4] 2 is a charge / discharge curve of the solid-state battery obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The solid-state battery and the solid-state battery system according to the present disclosure will be described in detail below.

[0022] A. Solid state battery FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery in the present disclosure. The solid-state battery 10 shown in FIG. 1 has a negative electrode AN having a negative electrode current collector 1, a positive electrode CA having a positive electrode active material layer 5 and a positive electrode current collector 6, and a solid electrolyte layer 4 arranged between the negative electrode AN and the positive electrode CA, and between the negative electrode current collector 1 and the solid electrolyte layer 4, a Mg layer 2 containing Mg and an Al layer 3 containing Al are arranged in this order from the negative electrode current collector 1 side. As shown in FIG. 1, the Mg layer 2 and the Al layer 3 can also be regarded as components of the negative electrode AN. The solid-state battery means a battery containing a solid electrolyte.

[0023] Moreover, the solid-state battery 10 is a battery that utilizes a deposition-dissolution reaction of metallic Li as the negative electrode reaction, and has the advantage of having a high energy density. When the solid-state battery 10 shown in FIG. 1 is charged, the solid-state battery 10 has a negative electrode active material layer 7 in which metallic Li (negative electrode active material) is deposited between the solid electrolyte layer 4 and the Mg layer 2. For example, as shown in FIG. 2, the solid-state battery 10 has a negative electrode active material layer 7 between the solid electrolyte layer 4 and the Al layer 3. That is, the negative electrode active material layer 7 contains deposited metallic Li.

[0024] According to the present disclosure, a solid-state battery capable of suppressing capacity reduction accompanying charge / discharge cycles is obtained by having an Mg layer and an Al layer in this order from the negative electrode current collector side between the negative electrode current collector and the solid electrolyte layer. As described above, in a solid-state battery using the deposition-dissolution reaction of metallic lithium as the negative electrode reaction, the metallic lithium layer deposited on the negative electrode current collector dissolves from the solid electrolyte layer side during discharge. Therefore, as the discharge progresses, a gap is likely to occur between the negative electrode current collector and the solid electrolyte layer. As a result, capacity reduction is likely to occur, particularly with repeated charge / discharge. Specifically, repeated charge / discharge may cause the gap to expand, resulting in a rapid capacity reduction. In addition, repeated charge / discharge may cause the metallic lithium layer to peel off from the solid electrolyte layer, making it impossible for the battery to function.

[0025] In contrast, in the present disclosure, the Mg layer and the Al layer are provided between the negative electrode current collector and the solid electrolyte layer in this order from the negative electrode current collector side, thereby suppressing the capacity decrease associated with the charge / discharge cycle. This is presumably due to the following reasons. As described above, a metallic Li layer (negative electrode active material layer) that is precipitated Li is generated between the solid electrolyte layer and the Al layer by charging. At this time, Li is also incorporated into the Mg layer and the Al layer. In addition, while Mg in the Mg layer is easily diffused into the metallic Li layer, Al in the Al layer is difficult to diffuse into the metallic Li layer. Therefore, the Al layer is present between the negative electrode current collector and the solid electrolyte layer in a state in which Li is incorporated after charging. In addition, the Al layer tends not to release the incorporated Li. Therefore, even if discharging proceeds, Li in the Al layer is appropriately left in the state, and the adhesion between the negative electrode and the solid electrolyte layer is likely to be good. Therefore, it is possible to suppress the expansion of the gap generated between the negative electrode current collector and the solid electrolyte layer due to repeated charging and discharging.

[0026] Furthermore, in the solid-state battery of the present disclosure, a plateau occurs at 3.2V to 3.0V in the discharge curve of the charge / discharge curve. Therefore, by setting the lower limit voltage during discharge higher than 3.0V, it becomes easier to prevent the battery from being completely discharged compared to conventional solid-state batteries. As a result, even if charging and discharging are repeated, the capacity reduction can be further suppressed. On the other hand, when the voltage of the solid-state battery reaches a predetermined voltage (e.g., 3.5V) as the discharge progresses, the voltage may suddenly drop. Even in such a case, since the plateau occurs, the lower limit voltage during discharge can be set lower than before, and the capacity characteristics of the solid-state battery can be utilized to the maximum extent.

[0027] 1.Negative electrode The negative electrode in the present disclosure has at least a negative electrode current collector. In addition, the negative electrode in the present disclosure preferably has, in order from the negative electrode current collector side, a Mg layer containing Mg and an Al layer containing Al. In addition, the negative electrode in the solid-state battery after charging preferably has a negative electrode active material layer of precipitated Li on the opposite side of the negative electrode current collector with respect to the Mg layer. In addition, the negative electrode may have a negative electrode active material layer of precipitated Li on the opposite side of the negative electrode current collector with respect to the Al layer.

[0028] (1)Mg layer The Mg layer in the present disclosure contains at least Mg. The Mg layer preferably contains Mg as a main component of metal elements. The ratio of Mg to all metal elements in the Mg layer is, for example, 50 atm% or more, may be 70 atm% or more, or may be 90 atm% or more.

[0029] The Mg layer may contain only Mg as a metal element, or may contain a metal element other than Mg. A typical example of a metal element other than Mg is Li. Usually, Li is taken into the Mg layer during the first charge to form an MgLi alloy. On the other hand, the Mg layer before the first charge may contain Li or may not contain Li. Other examples of metal elements other than Mg include Au, Cu, Fe, Ti, Zn, and Ni. The Mg layer may contain a nonmetal element such as O. The Mg layer may contain one type of element other than Mg, or may contain two or more types.

[0030] The Mg layer may be a Mg vapor deposition layer containing Mg. The Mg vapor deposition layer has a uniform thickness, and therefore has good adhesion to the negative electrode current collector. The Mg vapor deposition layer is usually formed by a vapor deposition method. The vapor deposition method may be physical vapor deposition such as vacuum deposition or sputtering, or may be chemical vapor deposition. Examples of the vapor deposition source include metallic magnesium and alloys containing magnesium and a metal other than magnesium. Like the Mg vapor deposition layer, the Mg layer in the present disclosure may be a layer that does not contain a conductive material (e.g., a carbon material). Similarly, the Mg layer in the present disclosure may be a layer that does not contain a binder (e.g., a polymer material).

[0031] The Mg layer may be a layer containing Mg-containing particles. The Mg-containing particles may be Mg simple particles or Mg alloy particles. The Mg alloy particles contain Mg and a metal element other than Mg. When the Mg layer is a layer containing Mg-containing particles, the Mg layer may or may not contain a conductive material. Similarly, the Mg layer may or may not contain a binder.

[0032] The Mg layer may be formed on a part of one surface of the negative electrode current collector, or may be formed on the entire surface. The coverage of the negative electrode current collector with the Mg layer is, for example, 70% or more, may be 80% or more, or may be 90% or more. It is preferable that the Mg layer is in direct contact with the negative electrode current collector. The thickness of the Mg layer is not particularly limited, but may be, for example, 0.5 μm or more, or 1 μm or more. On the other hand, the thickness of the Mg layer is, for example, 10 μm or less, or may be 5 μm or less.

[0033] (2) Aluminum layer The Al layer in the present disclosure contains at least Al. The Al layer preferably contains Al as a main component of metal elements. The ratio of Al to all metal elements in the Al layer is, for example, 50 atm% or more, may be 70 atm% or more, or may be 90 atm% or more.

[0034] The Al layer may contain only Al as a metal element, or may contain a metal element other than Al. A typical example of a metal element other than Al is Li. Usually, Li is taken into the Al layer during the first charge to form an AlLi alloy. On the other hand, the Al layer before the first charge may contain Li or may not contain Li. Other examples of metal elements other than Al include, for example, Sn, Si, Ti, Sc, etc. The Al layer may also contain a nonmetal element such as O. The Al layer may contain one type of element other than Al, or may contain two or more types.

[0035] The Al layer may be an Al vapor deposition layer containing Al. The Al vapor deposition layer has a uniform thickness, and therefore has good adhesion to the Mg layer. The Al vapor deposition layer is usually formed by a vapor deposition method. The vapor deposition method may be physical vapor deposition such as vacuum deposition or sputtering, or may be chemical vapor deposition. Examples of the vapor deposition source include metal aluminum and alloys containing aluminum and a metal other than aluminum. Like the Al vapor deposition layer, the Al layer in the present disclosure may be a layer that does not contain a conductive material (e.g., a carbon material). Similarly, the Al layer in the present disclosure may be a layer that does not contain a binder (e.g., a polymer material).

[0036] The Al layer may be a layer containing Al-containing particles. The Al-containing particles may be Al simple particles or Al alloy particles. The Al alloy particles contain Al and a metal element other than Al. When the Al layer is a layer containing Al-containing particles, the Al layer may or may not contain a conductive material. Similarly, the Al layer may or may not contain a binder.

[0037] The Al layer may be formed on a part of one surface of the negative electrode current collector, or may be formed on the entire surface. The coverage of the negative electrode current collector with the Al layer is, for example, 70% or more, 80% or more, or 90% or more. It is preferable that the Al layer is in direct contact with the Mg current collector. The thickness of the Al layer is not particularly limited, but may be, for example, 50 nm or more, 100 nm or more, or 260 nm or more. On the other hand, the thickness of the Al layer is, for example, 1 μm or less, 500 nm or less, or 400 nm or less.

[0038] (3) Negative electrode current collector Examples of the material of the negative electrode current collector include SUS (stainless steel), copper, nickel, and carbon. Examples of the shape of the negative electrode current collector include foil, mesh, and porous. The thickness of the negative electrode current collector is, for example, 0.1 μm or more, and may be 1 μm or more. If the thickness of the negative electrode current collector is too small, the current collecting function may be reduced. On the other hand, the thickness of the negative electrode current collector is, for example, 1 mm or less, and may be 100 μm or less. If the thickness of the negative electrode current collector is too large, the energy density of the solid battery may be reduced.

[0039] 2.Solid electrolyte layer The solid electrolyte layer in the present disclosure is a layer containing at least a solid electrolyte. The solid electrolyte layer may also contain a binder as necessary. The solid electrolyte layer may be in direct contact with the Al layer. A negative electrode active material layer, which is precipitated Li, may also be disposed between the solid electrolyte layer and the Al layer.

[0040] Examples of the solid electrolyte include inorganic solid electrolytes such as halide solid electrolytes, sulfide solid electrolytes, oxide solid electrolytes, and nitride solid electrolytes, and organic solid electrolytes such as polymer electrolytes and gel electrolytes. Among these, sulfide solid electrolytes are particularly preferred because they tend to have good adhesion to the negative electrode even as the discharge proceeds.

[0041] The sulfide solid electrolyte preferably contains, for example, Li, X (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen. The shape of the solid electrolyte may be, for example, particulate.

[0042] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-GeS2, Li2S-P2S5-SnS2, Li2S-P2S5-SiS2, Li2S-P2S5-LiI, Li2S-P2S5-LiI-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers; M is any of P, Si, Ge, B, Al, Ga, and In.) The above description of "Li2S-P2S5" means a material obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0043] The solid electrolyte may be glass, glass ceramics, or a crystalline material. Glass can be obtained by amorphous processing of a raw material composition (for example, a mixture of Li2S and P2S5). Examples of amorphous processing include mechanical milling. Mechanical milling may be dry mechanical milling or wet mechanical milling, but the latter is preferred. This is because it can prevent the raw material composition from adhering to the wall surface of a container or the like. Glass ceramics can be obtained by heat treating glass. Crystalline materials can be obtained, for example, by performing a solid-phase reaction process on the raw material composition. The solid electrolyte layer may contain one type of solid electrolyte, or two or more types. For example, it may contain both an inorganic solid electrolyte and an organic solid electrolyte.

[0044] The solid electrolyte is preferably in the form of particles. 50On the other hand, the average particle diameter (D 50 ) is, for example, 10 μm or less, and may be 5 μm or less. The Li ion conductivity of the solid electrolyte at 25° C. is, for example, 1×10 -4 S / cm or more, 1×10 -3 It is preferable that the viscosity is S / cm or more.

[0045] The content of the solid electrolyte in the solid electrolyte layer is, for example, 70% by weight or more, and may be 90% by weight or more. The solid electrolyte layer may contain a binder as necessary. Examples of the binder include fluorine-based resins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), and rubber-based resins such as acrylate butadiene rubber (ABR) and styrene butadiene rubber (SBR). The thickness of the solid electrolyte layer is, for example, 0.1 μm or more. On the other hand, the thickness of the solid electrolyte layer is, for example, 300 μm or less, and may be 100 μm or less.

[0046] 3.Positive electrode The positive electrode in the present disclosure preferably has a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer in the present disclosure is a layer containing at least a positive electrode active material. The positive electrode active material layer may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary.

[0047] The positive electrode active material is not particularly limited, but examples thereof include oxide active materials and sulfur-based active materials. Examples of oxide active materials include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co 0.1 Al 0.1 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 , Li(Ni 0.5 Mn 1.5)Spinel-type active materials such as O4, olivine-type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4 can be mentioned. Also, as the oxide active material, Li 1+x Mn 2-x-y M y O4 (M is at least one of Al, Mg, Co, Fe, Ni, and Zn, 0 < x + y < 2), a LiMn spinel active material represented by, or lithium titanate may be used.

[0048] Also, a coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because the reaction between the oxide active material and the solid electrolyte can be suppressed. Examples of the Li-ion conductive oxide include LiNbO3, Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coverage rate of the coating layer on the surface of the oxide active material is, for example, 70% or more, and may be 90% or more.

[0049] Also, the sulfur-based active material is an active material containing at least the S element. The sulfur-based active material may or may not contain the Li element. Examples of the sulfur-based active material include elemental sulfur, lithium sulfide (Li2S), and polysulfide lithium (Li2Sx, 2 ≤ x ≤ 8).

[0050] The proportion of the positive electrode active material in the positive electrode active material layer is, for example, 20% by weight or more, may be 30% by weight or more, and may be 40% by weight or more. On the other hand, the proportion of the positive electrode active material is, for example, 80% by weight or less, may be 70% by weight or less, and may be 60% by weight or less.

[0051] The conductive material may be, for example, a carbon material. Specific examples of the carbon material include acetylene black, ketjen black, VGCF, and graphite. The solid electrolyte and binder are the same as those described in "2. Solid electrolyte layer." The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0052] Examples of materials for the positive electrode current collector include Al, Ni, and C. Examples of the shape of the positive electrode current collector include a foil shape, a mesh shape, and a porous shape.

[0053] 4.Other configurations The solid-state battery in the present disclosure may further have a restraining jig that applies a restraining pressure to the positive electrode, the solid electrolyte layer, and the negative electrode along the thickness direction. A known jig can be used as the restraining jig. The restraining pressure is, for example, 0.1 MPa or more, and may be 1 MPa or more. On the other hand, the restraining pressure is, for example, 50 MPa or less, and may be 20 MPa or less, 15 MPa or less, or 10 MPa or less. The smaller the restraining pressure, the more the restraining jig can be prevented from becoming large. On the other hand, the smaller the restraining pressure, the more likely a short circuit is to occur, but the occurrence of a short circuit can be suppressed by providing the protective layer in the present disclosure.

[0054] 5. Solid state battery As shown in FIG. 1, the solid-state battery 10 has an anode current collector 1, an Mg layer 2 containing Mg, an Al layer 3 containing Al, a solid electrolyte layer 4, a cathode active material layer 5, and a cathode current collector 6 in this order. As shown in FIG. 1, the solid-state battery 10 does not need to have an anode active material layer between the solid electrolyte layer 4 and the Al layer 3. In particular, it is preferable that the solid electrolyte layer 4 and the Al layer 3 are in direct contact with each other. On the other hand, when the solid-state battery 10 shown in FIG. 1 is charged, the solid-state battery 10 has an anode active material layer 7 in which metal Li (anode active material) is precipitated between the solid electrolyte layer 4 and the Mg layer 2. For example, as shown in FIG. 2, the solid-state battery 10 has an anode active material layer 7, which is precipitated Li, between the Al layer 3 and the solid electrolyte layer 4.

[0055] The solid-state battery in the present disclosure is usually a lithium-ion battery. The solid-state battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery, since it can be repeatedly charged and discharged and is useful, for example, as an in-vehicle battery.

[0056] B. Solid-state battery systems The present disclosure provides a solid-state battery system including: a solid-state battery having a negative electrode with a negative electrode current collector, a positive electrode, and a solid electrolyte layer disposed between the negative electrode and the positive electrode, utilizing a deposition-dissolution reaction of metallic lithium as a negative electrode reaction; and a discharge control device that controls discharge of the solid-state battery, wherein the solid-state battery has, between the negative electrode current collector and the solid electrolyte layer, a Mg layer containing Mg and an Al layer containing Al, in this order from the negative electrode current collector side, and the discharge control device controls a lower limit voltage of the solid-state battery during discharge to be higher than 3.0 V.

[0057] According to the present disclosure, a solid-state battery system is provided in which the lower limit voltage during discharging of a specific solid-state battery is controlled to prevent the battery from being completely discharged.

[0058] The solid-state battery in the present disclosure is similar to the content described in "A. Solid-state battery" above, and therefore the description here is omitted. In the solid-state battery in the present disclosure, in a discharge curve with the horizontal axis representing the discharge capacity (mAh) and the vertical axis representing the voltage (V), a discharge plateau usually exists at 3.2 V to 3.0 V. In addition, the positive electrode active material layer in the present disclosure contains the above-mentioned positive electrode active material. The discharge reaction potential of the positive electrode active material is, for example, 3.5 V (vs Li / Li + The discharge reaction potential can be determined, for example, by cyclic voltammetry.

[0059] The discharge control device in the present disclosure controls the discharge of the solid-state battery. The discharge control device is usually configured to control the discharge of the solid-state battery based on the voltage of the solid-state battery. Specifically, the discharge control device controls the lower limit voltage of the solid-state battery during discharge to be higher than 3.0V. That is, the discharge control device controls the discharge of the solid-state battery so as to terminate the discharge before the voltage of the solid-state battery reaches 3.0V. The discharge control device may control the lower limit voltage of the solid-state battery during discharge to 3.05V or higher, or 3.15V or higher.

[0060] On the other hand, the discharge control device may control the lower limit voltage of the solid-state battery during discharge to 3.5 V or less, 3.4 V or less, or 3.3 V or less. By setting the lower limit voltage to the above value or less, the capacity characteristics of the solid-state battery can be utilized to the maximum.

[0061] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0062] [Example 1] (Preparation of negative electrode member) A SUS foil (SUS304) was prepared as a negative electrode current collector. Mg was evaporated onto the SUS foil to form a 1000 nm thick metallic Mg layer. Then, Al was evaporated onto the metallic Mg layer to form a 250 nm thick metallic Al layer. This produced a negative electrode member having, in this order, a metallic Mg layer as a first layer and a metallic Al layer as a second layer on the negative electrode current collector.

[0063] (Preparation of positive electrode components) A positive electrode active material (nickel-cobalt lithium aluminate (NCA), a sulfide-based solid electrolyte, and a conductive material (carbon) were wet-mixed in an organic solvent to prepare a positive electrode mixture. Next, the positive electrode paste was applied onto a positive electrode current collector (aluminum foil) by a blade method using an applicator. After application, the mixture was dried on a hot plate at 100°C for 30 minutes. This resulted in a positive electrode member having a positive electrode current collector and a positive electrode active material layer.

[0064] (Fabrication of solid-state batteries) A Li2S-P2S5-LiI-based sulfide solid electrolyte was prepared as the sulfide solid electrolyte. The powdered sulfide solid electrolyte was placed in an alumina cylindrical die (cross-sectional area: 1 cm 2 ), and then uniaxial compression molding was performed with a steel punch rod at a load of 10 kN to mold the solid electrolyte layer. Next, a positive electrode member was placed on one side of the molded solid electrolyte layer so that the positive electrode active material layer was on the solid electrolyte layer side, and then uniaxial compression molding was performed with a punch rod at a load of 10 kN to obtain a laminate of a positive electrode and a solid electrolyte layer. Next, a negative electrode member was placed on the other side of the solid electrolyte in the above laminate so that the Al layer was on the solid electrolyte layer side, and then uniaxial compression molding was performed with a punch rod at a load of 40 kN to produce a solid battery of Example 1 in which the positive electrode, solid electrolyte layer, and negative electrode were laminated.

[0065] [Examples 2 and 3] A solid-state battery was produced in the same manner as in Example 1, except that a negative electrode member in which the thicknesses of the metallic Mg layer and metallic Al layer formed on the negative electrode current collector were changed to those shown in Table 1 was used.

[0066] [Comparative Example 1] A solid-state battery was produced in the same manner as in Example 1, except that a negative electrode current collector (SUS foil) was used as the negative electrode member by depositing Mg onto the negative electrode current collector to form a metallic Mg layer having a thickness of 1000 nm.

[0067] [Comparative Example 2] A solid-state battery was fabricated in the same manner as in Example 1, except that a negative electrode current collector (SUS foil) was used as the negative electrode member by depositing Mg and Al (Mg:Al (molar ratio) = 90:10) to form a 1000 nm-thick Mg-Al alloy layer.

[0068] [Comparative Example 3] Al was evaporated onto the negative electrode current collector (SUS foil) to form a metal Al layer with a thickness of 250 nm. Next, Mg was evaporated onto the metal Al layer to form a metal Mg layer with a thickness of 1000 nm. This produced a negative electrode member having a metal Al layer as a first layer and a metal Mg layer as a second layer in this order on the negative electrode current collector. A solid-state battery was produced in the same manner as in Example 1, except that the obtained negative electrode member was used.

[0069] [Comparative Example 4] Mg was evaporated onto the negative electrode current collector (SUS foil) to form a 1000 nm thick metal Mg layer. Then, Ag was evaporated onto the metal Mg layer to form a 250 nm thick metal Ag layer. This produced a negative electrode member having a first layer, a metal Mg layer, and a second layer, a metal Ag layer, in this order, on the negative electrode current collector. A solid-state battery was produced in the same manner as in Example 1, except that the obtained negative electrode member was used.

[0070] [Table 1]

[0071] [evaluation] (Charge / discharge test) For the solid-state batteries of Examples 1 to 3 and Comparative Examples 1 to 4, a charge / discharge test was performed for 50 cycles under the following control conditions 1 and 2, the discharge capacity was measured, and the discharge capacity retention rate was calculated by the following formula A. The results are shown in Table 2.

[0072] <Control condition 1> Upper limit 4.2V, lower limit 3.0V, current: 2C, temperature: 60℃ <Control condition 2> Upper limit 4.2V, lower limit 3.2V, current: 2C, temperature: 60℃

[0073] (Formula A)R 50 =(C 50 / C1)×100 (In the above formula A, R 50 indicates the discharge capacity retention rate (%) of the solid-state battery at the 50th cycle, and C 50 indicates the discharge capacity at the 50th cycle of the solid-state battery, and C1 indicates the discharge capacity at the 1st cycle of the solid-state battery.)

[0074] 3 and 4 show the charge / discharge curves of the first cycle when the solid-state batteries of Example 1 and Comparative Example 1 were charged and discharged under Control Condition 1. A plateau was confirmed between 3.2 V and 3.0 V in the discharge curve of Example 1 in FIG. 3, but no plateau was confirmed between 3.6 V and 3.0 V in the discharge curve of Comparative Example 1 in FIG. 4. Similarly to the solid-state battery of Example 1, a plateau was confirmed between 3.2 V and 3.0 V in the solid-state batteries of Example 2 and Example 3.

[0075] [Table 2]

[0076] As shown in Table 2, it was confirmed that the solid state batteries of Examples 1 to 3 had higher capacity retention rates than those of Comparative Examples 1 to 3 under both Control Condition 1 and Control Condition 2. In Comparative Example 4, a short circuit occurred during the initial charge / discharge (NG).

[0077] In the case of using the solid-state batteries of Examples 1 to 3, it was confirmed that the capacity retention rate was particularly high when the lower limit voltage during discharge was controlled to 3.2 V (control condition 2) compared to when it was controlled to 3.0 V (control condition 1). This is believed to be because by performing charge and discharge with the lower limit discharge voltage set to 3.2 V, it is possible to prevent the battery from being completely discharged, and it is possible to further suppress the decrease in the capacity retention rate even when charging and discharging are repeated. [Explanation of symbols]

[0078] 1...Negative electrode current collector 2...Mg layer 3 … Aluminum layer 4 … Solid electrolyte layer 5 … Positive electrode active material layer 6 … Positive electrode current collector 7 … Negative electrode active material layer 10 … Solid battery

Claims

1. A solid-state battery comprising: a negative electrode having a negative electrode current collector; a positive electrode having a positive electrode active material layer and a positive electrode current collector; and a solid electrolyte layer disposed between the negative electrode and the positive electrode, the solid-state battery utilizing a deposition-dissolution reaction of metallic lithium as a negative electrode reaction, an Mg layer which is a vapor-deposited layer of metallic magnesium and an Al layer which is a vapor-deposited layer of metallic aluminum are disposed in this order from the negative electrode current collector between the negative electrode current collector and the solid electrolyte layer, The thickness of the Mg layer is 0.5 μm or more and 5 μm or less, The thickness of the Al layer is 100 nm or more and 500 nm or less, the solid electrolyte layer includes a sulfide solid electrolyte, The positive electrode active material layer comprises lithium nickel cobalt aluminate and a sulfide solid electrolyte.

2. a solid-state battery comprising: a negative electrode having a negative electrode current collector; a positive electrode having a positive electrode active material layer and a positive electrode current collector; and a solid electrolyte layer disposed between the negative electrode and the positive electrode, the solid-state battery utilizing a deposition-dissolution reaction of metallic lithium as a negative electrode reaction; A discharge control device that controls discharge of the solid-state battery; A solid-state battery system comprising: the solid-state battery has, between the negative electrode current collector and the solid electrolyte layer, an Mg layer which is a vapor-deposited layer of metallic magnesium, and an Al layer which is a vapor-deposited layer of metallic aluminum, in this order from the negative electrode current collector side, the Mg layer has a thickness of 0.5 μm or more and 5 μm or less, the Al layer has a thickness of 100 nm or more and 500 nm or less, the solid electrolyte layer contains a sulfide solid electrolyte, and the positive electrode active material layer contains lithium nickel cobalt aluminate and a sulfide solid electrolyte, The discharge control device controls a lower limit voltage of the solid-state battery during discharge to be higher than 3.0 V.

3. The solid-state battery system according to claim 2 , wherein the discharge control device controls a lower limit voltage of the solid-state battery during discharging to 3.5 V or less.

Citation Information

Patent Citations

  • All-solid battery

    JP2019087420A

  • All-solid battery and method for manufacturing the same

    JP2020184513A

  • All-solid battery

    JP2021051866A

  • Negative electrode layer for all-solid secondary battery, all-solid secondary battery including the same, and manufacturing method for the same

    JP2021077640A

  • Negative electrode and all-solid-state battery comprising the same

    KR1020210073664A